Analisis Coulomb Stress Change Nodal Plane 1 dan Nodal Plane 2 Pada Gempa Palu 7.5 Mw dan Pengaruhnya Terhadap Likuifaksi - Vegas Satrio Caniago; Rizky Mulya; Mhd Hadi Sabilil Haq; Rizki Wulandari (Universitas Andalas, 2026)
This study analyzes the Coulomb Stress Change (CSC) resulting from the Mw 7.5 Palu earthquake on September 28, 2018, to determine the actual fault plane and examine the spatial relationship between the distribution of stress changes and the locations of liquefaction. The data used were derived from the USGS catalog, which includes the mainshock and aftershocks, with the mainshock’s focal mechanism parameters strike, dip, and rake from two nodal planes, which were then processed using Coulomb 3.4 software, with an effective friction coefficient of 0.4. The results show that nodal plane 2 produced the highest percentage of aftershocks in the stress increase zone (ΔCS > 0) at 55.75%, higher than nodal plane 1 at only 40.7%, and its orientation is consistent with the direction of the Palu-Koro fault (NNW-SSE). Therefore, based on this, nodal plane 2 is interpreted as the actual fault plane of the main earthquake. Overlay analysis indicates that 3 of the 4 primary liquefaction sites Petobo, Lolu, and Jono Oge are located within the Coulomb stress increase zone based on nodal plane 2, suggesting a spatial association between the stress increase zone and liquefaction events, although a direct causal relationship cannot be concluded without further geotechnical validation. These findings suggest that Coulomb stress analysis has the potential to be used as an initial approach in identifying liquefaction-prone zones, particularly in areas with Geological conditions of water-saturated Quaternary alluvial deposits around active faults. The resulting stress distribution map can be used as supporting scientific data in disaster risk-based spatial planning and zoning of liquefaction-prone areas.